Weight loss and body composition change among workers undergoing a meal replacement dietary program: feasibility and efficacy - Vigna, Luisella; Cossovich, A; Barberi, C; Sommaruga, D; Neri, L; Conti, D; De Simone, F; Agnelli, GM; Riboldi, L (Progress in Nutrition, 2016)
Introduction. Partial meal replacements supplementing low calorie diets may be convenient for working people in time-constrained occupational settings. However, there is limited data obtained among non-obese, otherwise healthy subjects and very few real-life clinical studies corroborating findings from clinical experiments. Methods. We evaluated weight loss, glycemic control and body composition change among volunteer workers undergoing a 4-week low calorie diet followed by a 4-week maintenance regimen supplemented with meal replacements products. Results. Forty-two employees took part to the study and completed the 4-week intervention, whereas 36 completed the maintenance phase. Thirty-one patients (73.7%) experienced a weight loss greater than 3% of initial body mass. There was a reduction in serum glucose (Δ28d= -6.9 mg/dL, p<0.01), insulin resistance (Δ28d= -0.40, p<0.01), insulin (Δ28d= -1.54 pmol l−1, p<0.05), and fatty mass (Δ28d= -2.2%, p<0.01) after adjustment for potential confounders. There was negligible reduction in lean body mass (Δ28d=-0.3%, Δ60d=-0.2%; p for trend =0.54) and basal metabolic rate (Δ28d=-8.0, Δ60d=-6.0; p for trend =0.44). Conclusions. We observed significant weight loss during a 2-month intervention period. The dietary strategy was well accepted irrespective of age, dietary regimen and sex. We also observed a improvement in glycemic control, both among overweight and normal weight volunteers.